Primary and secondary scintillation of CF4-based mixtures in low-pressure gaseous detectors - Brunbauer, F. M.; Amedo, P.; Flöthner, K. J.; Gonzalez Diaz, D.; Janssens, D.; Leardini, S.; Lisowska, M.; Müller, H.; Oliveri, E.; Orlandini, G.; Pfeiffer, D.; Ropelewski, L.; et al. (Frontiers in Detector Science and Technology, 2025)
Optical readout of micro-pattern gaseous detectors relies on recording scintillation light emitted during electron avalanche multiplication with imaging sensors of high-granularity pixelated readout. It can be used in applications such as optical Time Projection Chambers for track reconstruction, low material budget beam monitoring or radiography, to name but a few. A good match between the scintillation light emission spectra and the spectral sensitivity of the recording devices is required to achieve high signal-to-noise ratios and ensure optimal acquisition parameters. Experimental requirements for operation at low or high pressures may have an impact on the scintillation spectra of gases commonly used for optical readout. We investigate the pressure dependence of scintillation light emission spectra of primary and secondary scintillation in the range of 1,000 mbar down to 25 mbar, in the wavelength range of 200 nm–800 nm. Primary scintillation spectra for different CF4-based mixtures are observed to be independent of pressure in the investigated range. A strong variation in the ratio of ultraviolet (UV) emission to visible (VIS) emission bands is observed as a function of pressure for secondary scintillation of CF4 and He/CF4 mixtures while for Ar/CF4 the overall light yield varies with an almost constant ratio between UV and VIS components. While the addition of low fractions of SF6 as electronegative drift gas does significantly lower the total light output, the shape of the emission spectra is not affected. The observed increase in relative UV emission for low pressure operation in CF4 and He/CF4 mixtures can guide the selection of optical readout devices or wavelength shifters for applications requiring low gas pressure operation.